Tinjauan Siyasah Dusturiyah Terhadap Proses Pembentukan Peraturan Desa Menurut Permendagri Nomor 111 Tahun 2014 - Alia Nur Afdholina; Dahrul Muftadin (Manabia: Journal of Constitutional Law, 2021)
Village regulations are a manifestation of Indonesia as a state of law. Its existence in the world of regional legal products is arguably still new and its existence is the answer to the challenges of the social conditions of society which always change from time to time. As a result of the issuance of Law number 12 of 2011 concerning the Formation of Legislation (UU PPPU), it shifted the hierarchy of the position of village regulations. This has an impact on the uncertainty of the juridical basis of village regulations. This has led to the neglect of this type of regional legal product, especially since it is still relatively new, often in the process of formation it is not in sync with the procedures contained in Minister of Home Affairs Regulation (Permendagri) Number 111 of 2014 and does not pay attention to the rules and principles of the formation of laws and regulations. From these problems, two problem formulations emerged, namely: 1) What is the Process of Formation of Village Regulations according to Permendagri Number 111 of 2014?, 2) How is Siyasah Duturiyah's Review of the Process of Formation of Village Regulations according to Permendagri Number 111 of 2014?. This research is library research in a qualitative form. To explore the data and analyze the data using a juridical-normative approach and Siyasah fiqh (Siyasah Duturiyah). The first results of this study are; the formation of village regulations must pay attention to 3 very fundamental and absolute rules or principles, namely the principle of lex superior derogate lex inferiori, principle of lex specialis derogate lex generalis, and principle of lex posterior derogate lex priori. The formation of village regulations according to Permendagri Number 111 of 2014 must go through 6 (six) stages, namely planning, preparation, discussion, determination and promulgation, dissemination, as well as evaluation and clarification. Second; based on the review of the dusturiyah siyasa on the substance of the process of forming village regulations, the principles of Islamic law have been realized, such as the application of the principles of deliberation and democracy. Because each stage does not leave the principle of amar ma'ruf nahi munkar. Even though in practice there are often legal defects and are used for personal and group interests only.